1996
DOI: 10.1177/106002809603000726
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid: A Migraine Prophylaxis Alternative

Abstract: While studies have noted possible benefits of valproate for migraine prophylaxis, most have small study samples (range 22-34 patients). The more recent, larger clinical trial confirms the effectiveness of valproate in the prevention of migraines. The available evidence suggests that valproic acid should provide another alternative to conventional migraine prophylaxis. However, it would still be beneficial to see other large studies conducted to determine valproate's place among the migraine prophylactic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It is also used to treat other neurological and psychiatric disorders such as bipolar affective disorder and migraine headache [417][418][419]. VPA is extensively metabolised by microsomal glucuronidation and mitochondrial -oxidation [420,421], while CYP-dependent -oxidation is a minor pathway (Fig.…”
Section: Valproic Acid (Vpa)mentioning
confidence: 99%
“…It is also used to treat other neurological and psychiatric disorders such as bipolar affective disorder and migraine headache [417][418][419]. VPA is extensively metabolised by microsomal glucuronidation and mitochondrial -oxidation [420,421], while CYP-dependent -oxidation is a minor pathway (Fig.…”
Section: Valproic Acid (Vpa)mentioning
confidence: 99%
“…Given that inhibition of histone deacetylases (HDACs) exerts neuroprotection in several brain disorders [33, 34], HDAC inhibitors (HDACi) including VPA have been investigated as a potential therapeutics for several neurodegenerative diseases [3335]. VPA is widely used to treat epilepsy, mood disorders, migraines and neuropathic pain [3639]. The molecular mechanism of VPA as therapeutics is not completely understood, but regulation of gamma-aminobutyric acid (GABA), activation of pro-survival protein kinases and inhibition of HDACs have been suggested [40, 41].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with rapid cycling bipolar disorder who do not often respond to lithium therapy, VPA is efficiently used as an alternative treatment or as an adjunctive agent to lithium and carbamazepine (CBZ) ( ). Furthermore, VPA was shown to be an effective treatment for the prevention of migraine headaches ( , ). A review of the literature in 1997 indicated a surge of interest in VPA treatment of bipolar affective disorders, mania, and prophylactic treatment of migraine and recurrent headaches.…”
Section: Introductionmentioning
confidence: 99%